Firm Dynamics in New Zealand: A Comparative Analysis with OECD Countries - Duncan Mills; Jason Timmins (New Zealand Government, The Treasury, 2004)
Previous work has suggested that New Zealand's firm dynamics and business demographics show a high proportion of small firms, small average firm size, and high rates of firm and employment turnover by comparison with other OECD countries. This paper reports on new comparative analyses of New Zealand's firm dynamics and business demography that attempt to control for measurement differences, using data from Statistics New Zealand's Business Demographic Statistics database, the OECD firm-level project, and the OECD's analysis of the Eurostat database. The variables investigated include firm size, firm turnover (entry and exit) rates, employment turnover rates, firm survival rates, and firm growth. The findings suggest that once measurement differences are taken into account, overall New Zealand's firm dynamics and demographics are broadly similar to many other OECD countries. Potential policy implications of these findings are discussed.
Keywords: L11; D21; 330; Firm Size; Firm Dynamics; Firm Growth; Entry and Exit